The Influence of Green Accounting, Environmental CSR, and Eco-Efficiency Strategy on Corporate Sustainability Performance - Nurul Hasanah; Farida Yulianti; Maria Yovita R. Pandin; Amiartuti Kusmaningtya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the influence of green accounting, environmental corporate social responsibility (CSR), and eco-efficiency strategy on corporate sustainability performance in Indonesia. The research employed a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Data were collected through a survey of 150 manufacturing and service companies that have implemented environmental reporting in their sustainability reports for the 2020–2024 period. The findings reveal that green accounting has a significant positive effect on sustainability performance, while environmental CSR strengthens this relationship through environmentally oriented social responsibility practices. Moreover, the eco-efficiency strategy plays a crucial role as a driver of resource efficiency in supporting long-term sustainability goals. The research model produced an R² value of 0.71, indicating that the combination of these three variables explains a substantial proportion of the variation in corporate sustainability performance. The implications of this study emphasize that the implementation of green accounting, environmental CSR, and eco-efficiency strategies not only enhances corporate reputation and regulatory compliance but also creates sustainable economic value for companies amid the green industrial transition era.